(untitled) (Shahroud Journal of Medical Sciences, 2020)
Background: The aim of study was to determine the effect of gradual reduction in sodium dialysate on occurrence of muscular cramp, and the serum level of calcium and magnesium in patients Undergoing hemodialysis. Methods: This triple-blinded cross-over clinical trial was conducted on 56 hemodialysis patients. After random allocation of patients into group A by the routine method (fixed sodium dialysate) and group B with gradual reduction in sodium dialysate, they underwent a 3-session dialysis. After one week of dialysis through routine method (wash out), patients underwent 3-session dialysis in group B by routine method and in group A by gradual reduction in sodium dialysate. Occurrence of muscular cramp was recorded by using a check list. Patients, serum level of calcium and magnesium before and after intervention was measured. Descriptive statistics indices and inferential statistics tests (repeated measures Analysis of variance) were used. Results: The rate of muscular cramp in routine method was 3.8% in one muscle, 1.9% in two or more muscles, and in the method of gradual reduction of sodium dialysate was 1.9% in one muscle, and 7.5% in two or more muscles. The mean difference of plasma calcium and magnesium before and after the dialysis with routine method was 0.43 and 0.26, respectively, and in the method of gradual reduction of sodium dialysate was 0.45 and 0.34. In this study no significant difference was observed for the rate of occurrence of muscular cramp and serum level of calcium and magnesium between two methods. Conclusions: The results showed that gradual reduction of sodium dialysate, has no effect on occurrence of muscular cramp during dialysis, serum level of calcium and magnesium in hemodialysis patients. Further investigations are needed to better understand the exact effect of this method, and also eliminate the study limitations. Keywords: Calcium, Hemodialysis, Magnesium, Muscle cramp, Sodium dialysate.